Commercial productivity and quality of pitaya as a function of number of fruits per cladode - Santos, Núbia Cassiana; Monteiro Cruz, Maria do Céu; de Almeida Alves, Deilson; Esdras Lima, João; Gonçalves Guimarães, Amanda (Revista Ceres, 2023)
Increasing orchard productivity is among the main objectives of pitaya producers. However, the commercial productivity may reduce due to reduction of fruit size as a function of the high amount per plant. This study evaluated the influence of the number of fruit per cladode in commercial productivity and in quality of fruits of two pitaya species at different harvest times. The experiment was carried out in a six-year-old orchard formed by the species Selenicereus undatus and Hylocereus polyrhizus. At each flowering time, the number of fruits set per cladode was counted and plants with two, four, five and six fruits per cladode were selected, and surplus fruits removed. The evaluations followed a split plot design over time, with the main plot as the number of fruit per cladode and the subplot as the harvest seasons: December, February and March, with four replicates and one plant per plot. Plants grown with two fruits per cladode presented the highest percentage of fruits with commercial size and commercial productivity. Both species showed fruits with commercial size in the first harvest of the cycle (December). S. undatus fruits classified as Class I and H. polyrhizus fruits classified as Extra and Class I showed the best quality.